Research of Thermal Hydraulic Conditions Effect on PWR CIPS Risk - Meng, Shuqi; Yan, Yalun; Hu, Yousen; Hu, Yisong; Ruan, Tianming (Frontiers in Energy Research, 2022)
In order to reveal the effect of thermal hydraulic conditions on the PWR CIPS risk, the evaluation of a PWR CIPS risk in the first cycle under different core flow rates, average primary temperatures, power levels, and primary pressures was conducted by combining thermal hydraulic codes LINDEN and CRUD (Chalk River unidentified deposit) analysis software CAMPSIS. The research result illustrating the essential effect of thermal hydraulic conditions on CIPS is changing the SNB (subcooled nucleate boiling) level of the fuel assembly’s surface; thus, boron precipitation and local power distribution will be affected. Theoretical evidence and statistical support of the effect of thermal hydraulic conditions on the PWR CIPS risk could be obtained via this research.